(untitled) (Revista de Educação Pública, 2012)
O presente artigo propõe uma reflexão sobre o modelo de avaliação da CAPES à luz do V Plano Nacional de Pós Graduação. O texto apresenta uma revisão das origens do modelo e, em seguida, relata as alterações efetuadas no período contemplado pelo referido plano. Por fim, discute os desafios que a CAPES enfrentará no futuro próximo, atrelados ao crescimento, à diversidade e assimetrias do sistema; à necessidade de conceituação da inserção social; à demanda por avaliações qualitativas e por articulações CAPES x SINAES e CAPES nova x velha, para assegurar a qualidade e a relevância da avaliação sob sua responsabilidade. Reflections on the CAPES Evaluation System from the perspective of the V National Plan for Graduate Education Abstract This article proposes to reflect on the CAPES evaluation model and its relationship to the V National Plan for Graduate Education. The text presents a review of the origins of the model and, subsequently, relates the alterations effectuated during the time period addressed by the said plan. In its conclusion, it discusses the challenges that CAPES will face in the near future in order to assure the quality and relevance of the evaluations for which it is responsible. Such challenges are linked to the growth, diversity and asymmetry of the system; the need to conceptualize social insertion; the demand for qualitative evaluations and for greater articulation between CAPES and SINAES and between the old and new CAPES. Keywords: Graduate studies. CAPES. Higher education evaluation.